SPECIAL EDUCATION ENROLL INDICATORS IN THE WESTERN AMAZON: POINTS AND COUNTERPOINTS - Barbosa Correa, Marcia de Fatima [UNESP]; Pinheiro, Karen Brissow; Sampaio de Oliveira, Anna Augusta [UNESP] (Fundacao Univ Tocantins, 2020)
The present study analyzes the enrollment indicators of students directed to special education, in the regular education network of the state of Rondonia, Western Amazon, between 2008 and 2018, highlighting the points and counterpoints of these data in relation to the studies described. The methodology used was literature review and document analysis, using Synopses from the Elementary School Census. The analysis was performed comparing the type of schooling of enrollments in special education, common classes and exclusive classes and specific category of the target audience of special education. The data revealed that, in the period studied, the situation in the state of Rondonia is similar to the national situation, indicating a higher number of enrollments in the category of intellectual disability, low growth rate and presenting only general indicators, with no data on the study of the evolution of enrollments., which would allow observing the movement of the special education target audience in their school process: enrollment-permanence-completion.
Keywords: Enrollment; Special Education; Rondonia; Western Amazon